(untitled) (Research, Society and Development, 2021)
The work of a military police officer can lead to the appearance of anxiety disorders. They can have significant impacts on police officers’ health, affecting their quality of life and social relationships, and can also affect their performance in terms of their duties and service activities and put their lives and that of third parties at risk. The present study aimed to analyze, through the literature, the scientific evidence of the factors associated with the emergence of anxiety/depression in military police officers. It was an integrative literature review, for which the following clinical question was formulated: “What is the scientific evidence on the factors associated with the emergence of anxiety/depression in military police officers?”. The databases were consulted, using descriptors and keywords, between the years 2015 to 2020, in Portuguese, Spanish and English. Thus, thirteen studies were included in this review, it was observed that military police officers reported suffering from anxiety/depression ranged from 19 to 50 years of age, females prevailed being more vulnerable to disorders, it was identified that police officers from the administrative sector and bureaucratic operational processes, are less likely to develop anxiety disorders or a pathological condition of depression, living with violence, the constant risk of death and excessive workloads are factors that cause stress, anxiety and can trigger depression affecting significantly the quality of life of these officers. Which allows us to conclude that all the results reported the need to optimize the work environment through awareness, promoting adequate knowledge about emotional disorders that are routine, making it possible to reduce the rates of illness in this category.